2013
DOI: 10.1038/ncb2879
|View full text |Cite
|
Sign up to set email alerts
|

Senescent cells harbour features of the cancer epigenome

Abstract: Altered DNA methylation and associated destabilization of genome integrity and function is a hallmark of cancer. Replicative senescence is a tumour suppressor process that imposes a limit on the proliferative potential of normal cells that all cancer cells must bypass. Here we show by whole-genome single-nucleotide bisulfite sequencing that replicative senescent human cells exhibit widespread DNA hypomethylation and focal hypermethylation. Hypomethylation occurs preferentially at gene-poor, late-replicating, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
302
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(331 citation statements)
references
References 69 publications
(111 reference statements)
26
302
1
2
Order By: Relevance
“…When analyzing the genomic distribution of dmCpGs and, in line with previously published reports (Cruickshanks et al., 2013; Kulis et al., 2012; Yuan et al., 2015), we found that hypomethylated CpGs were enriched at open sea DNA regions, principally intronic and intergenic, irrespective of the type of process. The distribution of hypermethylated CpGs was found to be similar to that of the array, which is to a certain extent to be expected because it was designed to interrogate a promoter‐ and CpG dense‐biased portion of the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing the genomic distribution of dmCpGs and, in line with previously published reports (Cruickshanks et al., 2013; Kulis et al., 2012; Yuan et al., 2015), we found that hypomethylated CpGs were enriched at open sea DNA regions, principally intronic and intergenic, irrespective of the type of process. The distribution of hypermethylated CpGs was found to be similar to that of the array, which is to a certain extent to be expected because it was designed to interrogate a promoter‐ and CpG dense‐biased portion of the genome.…”
Section: Discussionmentioning
confidence: 99%
“…While this molecular alteration preferentially occurs at gene bodies, intergenic DNA regions, and repeated DNA elements (Ehrlich, 2009) and is proposed to be associated with chromosomal instability, reactivation of transposable elements, and loss of genomic imprinting, its precise functional role in cancer development is still poorly understood (Rodríguez‐Paredes & Esteller, 2011). Intriguingly, global loss of genomic DNA methylation has also been reported during the aging and senescence process (Cruickshanks et al., 2013; Fraga & Esteller, 2007). Whole‐genome bisulfite sequencing and methylation arrays have confirmed the global loss of DNA methylation in different human tissues including blood (Heyn et al., 2012), mesenchymal stem cells, and brain (Fernández et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that a reason why transdifferentiation typically fails to shut off an initial genetic program may relate to the failure of resetting heterochromatic domains for new cell type . Understanding how heterochromatic regions are established and maintained will continue to provide insight into enhancing cell conversions and may help explain changes in cell fate in diseases such as cancer (Cruickshanks et al 2013). …”
Section: Repressive Chromatin Features For Pioneer Factor Bindingmentioning
confidence: 99%
“…Senescent fibroblasts are known to undergo methylation changes (Cruickshanks et al 2013), and these alterations may lead to epigenetic alterations that promote stochastic changes in gene expression. Alternatively, it has been suggested that DNA damage may modulate gene expression by altering the binding capacity of transcription factors (Rose et al 2012).…”
Section: The Senescent Phenotype and Promiscuous Gene Expressionmentioning
confidence: 99%